HUBUNGAN SIKAP DENGAN PELAKSANAAN LIMA PILAR PADA PENDERITA DIABETES MELLITUS DI PUSKESMAS NAIONI - KOTA KUPANG – NUSA TENGGARA TIMUR - Yohanes Dion (NHM PRESS, 2021)
The program of implementing the five pillars of diabetes mellitus in Indonesia has been implemented in 2011. However, the implementation has not been optimally implemented, this is because sufferers find it difficult to do because with the condition of the disease they experience a lifetime, sometimes boredom arises in undergoing treatment and various rules related to diabetic management. The purpose of this study was to analyze the relationship between attitudes and management of the five pillars of diabetes mellitus sufferers at Naioni Health Center - Kupang. This research design used was quantitative research through a cross- sectional approach. The Samples were taken using a total sampling technique of 52 respondents. The data Thwith collection by using questionnaire sheets, and analyzed the data reseaecher used the Spearmen Rhank statistical test. Based on the results of statistical test analysis, the analysis, the results obtained P value = 0.000 less than value α = 0.05, (p <0.05). This means that there is a relationship between attitude and management of the five pillars in people with diabetes mellitus. The advice given to patients to be able to comply with every recommendation from health workers in the management of the five pillars of diabetes mellitus.